Children safety risk factors in Khorasan Razavi province - Ali Zayerzadeh (19774491) (2015)
Although there has been a decline in the popularity of walking, it remains a very commonly employed mode of travel and people of almost all ages and sexes walk. Walking almost inevitably involves crossing a road, where the desire line of the pedestrian conflicts with the higher speed. Where speeds are high, this can result in either delay or risk for the pedestrian and when pedestrians are children the situation becomes more complicated. Sound transportation safety policies depend on appropriate knowledge to assess the potential effectiveness of safety programs. Since children have lower abilities to detect and determine speed of vehicles they could be at risk more than other road users. Also educational programs for children vary by their age groups and as they grow up they'll have more abilities to learn new things about coping with road risks and have more experience to save themselves. This study focused on the severity of injuries and fatalities incurred by children colliding with motor vehicles. The paper includes a review of the literature and a description of new research carried out on correlates of injury severity and measures of their relative effects on fatal or high injury collisions. The study focused on rural roads in Khorasan Razavi province. Data came from police records and forensic medicine processed from 2010 to 2015. Analysis of reported accidents during recent years showed that the number of traffic accidents sharply decreased that could be a result of educational programs along with traffic calming measure around schools. However, increase or decrease in number of fatalities or accidents could be interpreted in different ways by we need strong evidences using scientific methods to analyze the results and follow the best practices. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.3